Analisis Produktivitas Usaha Penangkapan Ikan Jaring Insang (Gill Net) dan Salambau (Trap Net) di Danau Marang, Kota Palangka Raya - Ummi Suraya; Sweking Gandi; Windi Tiara (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2018)
This study was aimed to analyze the productivity, influence factors of the catch and profit level of fishing business in gill net and trap net. This research was conducted for two month, in February-March 2018 with 4 sampling at Lake Marang, Marang Village, Bukit Batu Sub-District of Palangka Raya Municipality. The results of the research in Lake Marang indicated that the productivity of gill net fishing gear amounted to 8.67 Kg and trap net fishing gear amounted to 23.33 Kg in 2017. Based on the interviews with 10 fishermen as respondents, shows profit income of Rp. 4,212,000 per year, while relative profit business (Revenue Cost Ratio (R/C)) obtained average at 2. Analysis show that point of both fishing gears are eligible (value R/C >1). In a whole, income generally by gill net and trap net are enough to cover the expense of operational cost. Keywords : Business analyze, fishing gear, profit income, Revenue Cost Ratio.